Diálogos com as memórias da ditadura militar : a construção de um jogo para o ensino de história no nível médio - Cruz, Fernando de Souza (2021)
This dissertation presents the research and construction of a board game, aimed at the third grade of High School, which addresses the relationship between Memory and History Teaching, encompassing the Civil-Military Coup and Military Dictatorship (1964 to 1985). The study was motivated by past memories - individual or collective - derived from primitive and exemplary historical consciousnesses mobilized by students to confront the validity of historiographical production and History Teaching. Such manifestations demeaned the study of this period by adopting historical empathy as a method. Through the interlocution on the board game between memories collected by the National Truth Commission (CNV), journalistic photographs of recent protests against and in favor of the Military Dictatorship, written evidence produced between 1964 and 1985, recommendations present in the final report of the CNV and the Universal Declaration of Human Rights, “historical hypotheses” will be created about the beliefs, reasons and values in the past of the CNV witnesses, which will allow teachers to approach the period that demonstrates the multiplicity of parts of the past, humanizing history and defending human rights.